Positive influence of neuromuscular training on knee injury risk factors during cutting and landing tasks in elite youth female handball players - Schmidt, M.; Nolte, K.; Terschluse, B.; Willwacher, S.; Jaitner, T. (German Journal of Exercise and Sport Research, 2023)
Anterior cruciate ligament (ACL) ruptures are frequent in the age group of 15-19 years, particularly for female athletes. Although injury-prevention programs effectively reduce severe knee injuries, little is known about the underlying mechanisms and changes of biomechanical risk factors. Thus, this study analyzes the effects of a neuromuscular injury-prevention program on biomechanical parameters associated with ACL injuries in elite youth female handball players. In a nonrandomized, controlled intervention study, 19 players allocated to control (n= 12) and intervention (n= 7) group were investigated for single- and double-leg landings as well as unanticipated side-cutting maneuvers before and after a 12-week study period. The lower-extremity motion of the athletes was captured using a three-dimensional motion capture system consisting of 12 infrared cameras. A lower-body marker set of 40 markers together with a rigid body model, including a forefoot, rearfoot, shank, thigh, and pelvis segment in combination with two force plates was used to determine knee joint angles, resultant external joint moments, and vertical ground reaction forces. The two groups did not differ significantly during pretesting. Only the intervention group showed significant improvements in the initial knee abduction angle during single leg landing (p= 0.038: d= 0.518), knee flexion moment during double-leg landings (p= 0.011; d= -1.086), knee abduction moment during single (p= 0.036; d= 0.585) and double-leg landing (p= 0.006; d= 0.944) and side-cutting (p= 0.015;d= 0.561) as well as vertical ground reaction force during double-leg landing (p= 0.004; d= 1.482). Control group demonstrated no significant changes in kinematics and kinetics. However, at postintervention both groups were not significantly different in any of the biomechanical outcomes except for the normalized knee flexion moment of the dominant leg during single-leg landing. This study provides first indications that the implementation of a training intervention with specific neuromuscular exercises has positive impacts on biomechanical risk factors associated with ACL injury risk and, therefore, may help prevent severe knee injuries in elite youth female handball players.